(untitled) (Journal of Analytical Oncology, 2022)
Epidermal growth factor receptor (EGFR) has received significant attention for its therapeutic potential for pain relief. The relief of neuropathic pain after treatment with anti-EGFR antibodies or tyrosine kinase inhibitors has been previously described. However, few reports have investigated the association of cancer-related nociceptive pain or chronic chemical induced peripheral neuropathy with the analgesic effects of EGFR inhibition. Therefore, we conducted a retrospective survey of 191 patients with colorectal cancer receiving chemotherapy plus molecular targeting drugs to examine the analgesic effects of anti-EGFR antibodies against either cancer pain or oxaliplatin-induced peripheral neuropathy. We identified a significant difference in the improvement rates of nociceptive pain between panitumumab- and bevacizumab-treated patients (100% vs. 9.1%; p < 0.01), but not oxaliplatin-induced peripheral neuropathy. In conclusion, panitumumab may be effective at reducing cancer-related nociceptive pain.